Properties of medium density fiberboard (MDF) from sumble and eucalyptus wood / Nur ‘Aina Syifa’ Mohamed Sapari - Mohamed Sapari, Nur ‘Aina Syifa’ (2021)
Due to a scarcity of raw materials and the high demand for MDF in Pakistan, fast-growing species such as sumble and eucalyptus were used to create MDF. The purpose of this research was to examine the product's durability and to assess the impact of press plate, line speed, fibre moisture level, and glue ratio on MDF's Modulus of Rupture (MOR), Modulus of Elasticity (MOE), and Internal Bonding (IB). Bending and internal bonding tests were used to establish mechanical qualities, which were subsequently followed by data collection. The data is used to understand the board's MOR, MOE, and IB readings. Overall, the results suggest that there was no substantial influence due to the sustainability of fast-growing species as the raw material, as evidenced by mechanical qualities that meet the MDF standard's minimal requirements (EN 622 - 5:2016)